Proceedings of the 1997 IEEE/RSJ International Conference on Intelligent Robot and Systems. Innovative Robotics for Real-World
DOI: 10.1109/iros.1997.649098
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of part motion on a longitudinally vibrating plate

Abstract: Abstract-We analyze the dynamics of part motion for a novel type of planar parts feeder consisting of a longitudinally vibrating flat plate and a part placed on its surface. For each vibration cycle, the plate's velocity is held positive (forward motion) for a longer time than it is held negative (backward motion). This type of asymmetric vibration combined with the non-linear nature of Coulomb friction causes the part to accelerate along a straight line to a terminal velocity called the "feed rate". The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…In the simplest one-DoF case, the plate is horizontal and translates longitudinally. Reznik and Canny examined a particular type of bang-bang motion for this case in [13] and [14]. Okabe et al looked at one-DoF plate motion in which the plate is also angled with respect to the horizontal [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the simplest one-DoF case, the plate is horizontal and translates longitudinally. Reznik and Canny examined a particular type of bang-bang motion for this case in [13] and [14]. Okabe et al looked at one-DoF plate motion in which the plate is also angled with respect to the horizontal [15].…”
Section: Introductionmentioning
confidence: 99%
“…Canny's group showed that longitudinally vibrating plates can generate a rich vocabulary of programmable force fields [51], and they developed sophisticated dynamic models and dynamic simulators for micro actuator arrays and macroscopic vibrating plates [50]. Kavraki explored the power of elliptic fields capable of posing any part into one of two equilbrium states [33].…”
Section: Discussionmentioning
confidence: 99%
“…This group-within which this article corresponds-includes publications by Reznik et al [7], Huang and Mason [8], Baksys and Puodziuniene [9], Wolfsteiner and Pfeiffer [10], Lim [11], Paleta Hernández [12], Moll and Erdmann [13], and Han and Lee [14]. The best known approach in classical dynamics is a PhD Thesis [12].…”
Section: Introductionmentioning
confidence: 99%